2011
DOI: 10.1186/1472-6882-11-78
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary examination of the efficacy and safety of a standardized chamomile extract for chronic primary insomnia: A randomized placebo-controlled pilot study

Abstract: BackgroundDespite being the most commonly used herbal for sleep disorders, chamomile's (Matricaria recutita) efficacy and safety for treating chronic primary insomnia is unknown. We examined the preliminary efficacy and safety of chamomile for improving subjective sleep and daytime symptoms in patients with chronic insomnia.MethodsWe performed a randomized, double-blind, placebo-controlled pilot trial in 34 patients aged 18-65 years with DSM-IV primary insomnia for ≥ 6-months. Patients were randomized to 270 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 32 publications
0
57
2
5
Order By: Relevance
“…The effects of Chamomile tea on the 'calm' mood dimension were predicted and match the herbs historical reputation as a mild sedative and limited evidence from scientific investigation (Zick et al, 2011). The effect size was again moderate and reflects both an increase in calmness in the Chamomile condition combined with a decrease in the control and Peppermint conditions.…”
Section: Discussionmentioning
confidence: 95%
“…The effects of Chamomile tea on the 'calm' mood dimension were predicted and match the herbs historical reputation as a mild sedative and limited evidence from scientific investigation (Zick et al, 2011). The effect size was again moderate and reflects both an increase in calmness in the Chamomile condition combined with a decrease in the control and Peppermint conditions.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, the authors analyzed Hamilton Depression Rating Scale (HAM-D) scores in the same study and reported that chamomile significantly decreased depression scores as well (Amsterdam et al, 2012). As for insomnia, one RCT in 34 patients with primary insomnia examined the effect of chamomile (Zick et al, 2011). Chamomile showed small to moderate effectsize (Cohen's d≤0.20 to <0.60) improvement on sleep latency, night time awakenings, and fatigue severity scores, but no significant beneficial effects were observed in total sleep time, sleep efficiency, sleep latency, wake after sleep onset, sleep quality, and number of awakenings.…”
Section: Chamomile (Matricaria Recutita L)mentioning
confidence: 99%
“…Other potential pathways include its cholesterol-lowering, antioxidant, and anti-platelet properties which may convey cardiovascular benefits; however, we did not observe a positive effect on cardiovascular disease mortality after controlling for other factors. Chamomile has also demonstrated the potential to improve daytime functioning in patients with chronic insomnia (Zick, Wright, Sen, & Arnedt, 2011). No population based studies exist examining the association of chamomile consumption with overall and cause-specific mortality.…”
Section: Discussionmentioning
confidence: 99%